(untitled) (Castilla. Estudios de Literatura, 2021)
This essay analyzes the way in which the notions of nostalgia, utopia, and plot coherently articulate the entirety of Ricardo Piglia’s work. It is pointed out how these concepts link the three fundamental practices on which his poetics are built: reading, writing and teaching. With this, it is intended to collectively demonstrate that the fictional project of the Argentine author advocates reading as a practice of interpretation, whose theory germinated during the 60s while collaborating with the magazine Los Libros and, years later, Piglia developed more explicitly in his literature classes to translate it, ultimately, into his fiction.